(untitled) (Research, Society and Development, 2020)
Objective: To compare the efficacy of photobiomodulation and occlusal splint in patients with TMD-associated myofascial pain. Material and methods: 23 patients were randomized into 2 groups: laser group (LG) (n = 12) and occlusal splint group (OSG) (n=11). For the LG, laser was applied to 3 points on each side of the face. Twelve applications were made, 2 sessions per week. In the OSG, patients were instructed to use the device during sleep, 8 hours per night, for a period of 6 weeks, and 12 adjustment and follow-up sessions were performed. Patients in both groups were reevaluated 30 days after the end of the treatments. Results: There was a decrease in pain intensity, according to a visual analogue scale, in both groups before and after 1 month (LG, p = 0.008 and OSG p = 0.002), but with no difference between groups. For the quality of life, both treatments had a positive impact, with this impact being higher in the LG compared to the OSG (p <0.05). Regarding the cost-effectiveness analysis, laser was more cost-effective than the occlusal splint in the clinical trial. The incremental cost of the laser was 3,483.45 compared to the splint, but it had a cost ratio of 4,569.02 for controlled pain intensity while the splint showed 6,691.91 ratio for controlled pain intensity. Conclusion: The photobiomodulation was more cost-effective in controlling painful symptoms in patients with TMD and myofascial pain.